Emission Factors for a Taxi Fleet Operating on Liquefied Petroleum Gas (LPG) as a Function of Speed and Road Slope - Papadopoulos, Georgios; Keramydas, Christos; Ntziachristos, Leonidas; Lo, Ting-Shek; Ng, Kwok-Lam; Wong, Hok-Lai Anson; Wong, Carol Ka-Lok (Frontiers in Mechanical Engineering, 2018)
Real-driving emissions of NOx, CO and THC, as well as fuel consumption (FC) were studied from 18 liquefied petroleum gas (LPG) fueled taxis operating in a metropolitan road network. Euro 2 to Euro 5 technology vehicles were measured with the use of portable emission measurement systems (PEMS). Statistical processing was implemented to derive mean emission levels for the different technologies. The taxis were measured from 6 months to 2.5 years after their catalysts and lambda sensors were replaced. Τhe emission levels of Euro 4 taxis after catalyst replacement appear higher compared to pre-replacement levels, while pre-Euro 4 taxis emission levels were moderately reduced by the catalyst replacement. Overall, Euro 5 LPG taxis exhibit the lowest emissions, even below the respective regulated limits. The NH3 and N2O pollutant levels of a Euro 5 LPG taxi measured in the lab were found at about half its NOx emissions. Different integration methods of PEMS data were investigated towards the development of emission factors, including both time-based and distance-based approaches at different resolutions. Distance-based integration in sections of 500 m was considered suitable, as this provides a large dataset for statistical confidence and sufficient resolution for link-based modelling. Based on this, FC and emission factors of NOx, CO and THC as a function of speed and road slope are presented, separately for vehicles considered as normal and high emitters. Volatile organic compounds speciation of Euro 5 taxis showed that methane and butane are the most abundant hydrocarbon species in the exhaust.